(untitled) (Functional Plant Breeding Journal, 2022)
The subject of the present work is ventilator-associated pneumonia. The methodology that was adopted in the formulation of the work was based on bibliographical research, through consultations in books, magazines, search of manuals, treatises, articles published on the internet. Thus, the general objective of this paper seeks to present and highlight ventilator-associated pneumonia. The specific objectives seek to present and conceptualize the etiology, pathophysiology and evaluation related to ventilator-associated pneumonia, as well as to present its diagnostic methods and finally, briefly, to point out its treatment methods. Finally, the present research keeps the theme open, and it is proposed that, in the future, a new research will be carried out in order to update or contextualize the points discussed here. It is also proposed to carry out a case study, in order to contextualize what was studied here in practice.